Turismo Cultural y su incidencia en el comportamiento del consumidor del sector turístico de la provincia de Cotopaxi. - Ortiz Gavilanes, Andrés Alejandro (2018)
Cultural tourism is currently a factor that affects the development of the country. This lies in the manifestation of the culture, heritage, history and traditions of a certain place. In this document it is projected to determine the behavior of the visitor of cultural tourism and its incidence in the behavior of the consumer. Extrapolating the data identified to the rest of tourists who visit the province of Cotopaxi motivated by culture in all its elements. Research that reaches its development through an empirical study of transversal, quantitative and correlational type; which influenced the relationship between variables. In the same order of ideas, in the present study an analysis of cultural tourism was carried out with the following dimensions: (a) cultural sites-museums, monuments, architecture; (b) religious art -painting and sculpture- and (c) performing arts and expressions -music, theater, dance, handicrafts and popular festivals-; all of them immersed in the cultural environment of the province of Cotopaxi. At the same time, consumer behavior was assessed through the following dimensions: (a) satisfaction, (b) commitment and (c) loyalty; and that were calculated with an overall Cronbach's Alpha coefficient of 0.955; settling at an adequate level of reliability. The collection of the information was carried out with a survey applied to 384 foreign tourists, data obtained through a probabilistic sampling, which are processed through a statistical analysis of the variables in the SPSS25 program. Determining at the end the level of satisfaction, commitment and loyalty that tourists who arrive in the province of Cotopaxi have, motivated by knowing both natural and cultural attractions; thus identifying the consumer behavior of cultural tourism.